Hubungan Persepsi Orang Tua Tentang Pendidikan Anak Usia Dini di Raudhatul Athfal Darul Abror NW Gunung Rajak - Arnianti, Arnianti; Mariani, Mariani (ALSYS, 2021)
The purpose of this study was to examine the relationship between parents' perceptions of PAUD in Raudhatul Athfal Darul Abror NW Gunung Rajak. This type of research is correlational with a quantitative approach. Based on data analysis, the correlation coefficient between parents' perceptions of early childhood Islamic education to send their children to school is 0.879 and the coefficient of determination is 0.773. The result is that parents' perceptions of early childhood Islamic education are 87.9% of early childhood Islamic education to send their children to significant levels of 5%. It can be concluded that the perception of parents about having a significant relationship with early childhood Islamic education is 87.9%